2019
DOI: 10.1029/2019tc005641
|View full text |Cite
|
Sign up to set email alerts
|

The Decollement Depth of Active Thrust Faults in Italy: Implications on Potential Earthquake Magnitude

Abstract: Thrust fault ruptures during earthquakes do not often propagate down to the brittle‐ductile transition. Lithological variations control the behavior and depth of regional basal thrusts and decollement planes. Thrust fronts may be discontinuous along strike, limiting the dimension of single coseismic ruptures. These factors control the maximum expected magnitude in one region. This is the case of Italy where the convergence of few millimeter per year in the Apennines accretionary prism and along the retrobelt o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 126 publications
(183 reference statements)
1
8
0
Order By: Relevance
“…Our findings of localized shortening-related uplift are in line with some of the recent literature which, exploiting seismological, geophysical, and/or morphotectonic analyses, conclude that shortening at the boundary between the central and southern Apennines can be possibly accommodated by seismogenic faults [48,51,168,169]. Differently, they are difficult to explain with long-wavelength regional uplift eventually related to dynamic processes (see [127] among the others; see Section 2.1 for more extensive literature) in the central-southern Apennines.…”
Section: Tectonic Implications Of the Evidence Of Upliftsupporting
confidence: 91%
“…Our findings of localized shortening-related uplift are in line with some of the recent literature which, exploiting seismological, geophysical, and/or morphotectonic analyses, conclude that shortening at the boundary between the central and southern Apennines can be possibly accommodated by seismogenic faults [48,51,168,169]. Differently, they are difficult to explain with long-wavelength regional uplift eventually related to dynamic processes (see [127] among the others; see Section 2.1 for more extensive literature) in the central-southern Apennines.…”
Section: Tectonic Implications Of the Evidence Of Upliftsupporting
confidence: 91%
“…These lines of thought are in agreement with present‐day seismic and kinematic observations. For example, present‐day seismic activity is predominantly centered to the south of the Alps (Figures 1b and 2c; Danesi et al., 2015; Petricca et al., 2019). GPS‐based kinematics of upper lithospheric deformation (Nocquet & Calais, 2004) suggest the regions of highest strain are at the southernmost extent of TRANSALP.…”
Section: Discussionmentioning
confidence: 99%
“…In this view, the outermost ramp of the northern Apennines belt in the studied marine region may be a potential seismic source, although other more internal thrust faults could be potentially seismic as well. Considering the detachment depth (Petricca et al, 2019), we cannot exclude, along these structures, seismic events, similar to the Mw 6.0 and Mw 5.8 2012 Emilia earthquakes (e.g., Govoni et al, 2014; Pezzo et al, 2013, 2018) and to those reported in the historical seismic catalog (e.g., Camassi et al, 1991 and references therein, Molin et al, 2008), even though seismic reflection profiles in our and previous studies (Di Bucci & Mazzoli, 2002 and references therein) show no evidence of active tectonic deformations. This lack of evidences in the recent Quaternary deposits could be related to the effect of the large increase of sediment supply in the foredeep during the Quaternary eustatic low stand, which eventually produced a smaller apparent fault throw or masked the internal tectonic deformation (Scrocca et al, 2007).…”
Section: Discussionmentioning
confidence: 99%